Androgen receptor mRNA expression in urothelial carcinoma of the bladder: a retrospective analysis of two independent cohorts - Sikic, Danijel; Erben, Philipp (Translational oncology, 2019)
Introduction: Gender-specific differences have led to the androgen receptor (AR) being considered a possible factor in the pathophysiology of urothelial carcinoma of the bladder (UCB), but the exact role remains unclear. Materials and methods: The association of AR mRNA expression with clinicopathological features was retrospectively analyzed in two previously described cohorts. The first cohort consisted of 41 patients with all stages of UCB treated at Aarhus University Hospital, Denmark. The second cohort consisted of 323 patients with muscle-invasive bladder cancer (MIBC) accumulated by the Cancer Genome Atlas (TCGA) Research Network. Results: AR mRNA expression is significantly higher in non-muscle-invasive bladder cancer (NMIBC) when compared to MIBC (P=.0004), with no relevant changes within the different stages of MIBC. AR mRNA expression was significantly associated with TCGA molecular subtypes (P<.0001). In the total cohort, there was no association between AR expression and gender (P=.23). When analyzed separately, females showed a significantly worse disease-free (P=.03) and overall survival (P=.02) when expressing AR mRNA above median level, while the same was not observed for men. Multivariable Cox's regression analyses revealed AR mRNA expression to be an independent prognostic marker for disease-free survival in women (P=.007). Conclusions: AR mRNA expression is significantly higher in NMIBC than in MIBC, while high AR mRNA expression is associated with worse survival in females with MIBC. Further studies need to investigate the gender-specific role of AR in UCB.
Gesehen am 03.04.2019